Contributions of ammonia to high concentrations of pm2.5 in an urban area - Park, Junsu; Kim, Eunhye; Oh, Sangmin; Kim, Haeri; Kim, Soontae; Kim, Yong Pyo; Song, Mijung (Atmosphere, 2021)
Atmospheric ammonia (NH3 ) plays a critical role in PM2.5 pollution. Data on atmospheric NH3 are scanty; thus, the role of NH3 in the formation of ammonium ions (NH4+ ) in various environments is understudied. Herein, we measured concentrations of NH3, PM2.5, and its water-soluble SO42−, NO3−, and NH4+ ions (SNA) at an urban site in Jeonju, South Korea from May 2019 to April 2020. During the measurement period, the average concentrations of NH3 and PM2.5 were 10.5 ± 4.8 ppb and 24.0 ± 12.8 µg/m3, respectively, and SNA amounted to 4.3 ± 3.1, 4.4 ± 4.9, and 1.6 ± 1.8 µg/m3, respectively. A three-dimensional photochemical model analysis revealed that a major portion of NH3, more than 88%, originated from Korea. The enhancement of the ammonium-to-total ratio of NH3, NHX (NHR = [NH4+ ]/[NH4+ ] + [NH3 ]) was observed up to ~0.61 during the increase of PM2.5 concentration (PM2.5 ≥ 25 µg/m3 ) under low temperature and high relative humidity conditions, particularly in winter. The PM2.5 and SNA concentrations increased exponentially as NHR increased, indicating that NH3 contributed significantly to SNA formation by gas-to-particle conversion. Our study provided experimental evidence that atmospheric NH3 in the urban area significantly contributed to SNA formation through gas-to-particle conversion during PM2.5 pollution episodes.
Keywords: Ammonium ions; Atmospheric ammonia; Average concentration; Photochemical modelling; PM 2.5; South Korea; Urban; Urban areas; Urban site; Watersoluble; Aerosol pollution; Ammonia; Ammonium nitrate; PM2.5; Urban